Stacked Fields of Criminal Justice: The National Embeddedness of Transnational Policing - Christensen, Mikkel Jarle (International criminal justice review, 2022)
This article investigates how transnational policing is structured by the embeddedness of participating police units in national fields of criminal justice. Empirically, the analysis zooms in on the embeddedness and positionality of three different Danish police units that frequently engage in transnational cooperation. Positioned differently in the national field of criminal justice, these units have distinct capacities with regard to mobilizing and deploying material and symbolic resources and, consequently, have distinct modes of engagement with transnational policing. Conceptually expanding this insight to capture the structure of transnational policing more generally, this article develops the concept of “stacked fields” to capture how transnational cooperation and power relations are formatted by the national, institutional, and positional embeddedness of participating police units and agents.